Vulvodynia: diagnosis and therapy. Part 2 - Wachowska, Katarzyna; Florkowski, Antoni; Orzechowska, Agata; Talarowska, Monika; Berent, Dominika; Depko, Andrzej; Moczulska, Hanna; Michalska, Tamara; Gałecki, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
Vulvodynia is a chronic disorder involving pain or discomfort, characterized by a feeling of burning, stinging or irritation in the female genitalia in cases where there is no infection or skin disease of the vulva or vagina causing these symptoms. Vulvodynia is a clinical syndrome, which according to current estimates can occur in 15% of women. Clinical observations indicate the existence of different subtypes of vulvodynia distinguished based on their etiology. The multidimensional impact of this disease on the functioning of women is indicated, yet there are no clear answers as to its etiology, effective treatments, prevention and dissemination. The authors review the most important information about vulvodynia. In this part of the article characteristic symptoms that constitute the clinical picture of vulvodynia are described. The fundamental issue for such a diagnosis is to exclude in a physical examination any identifiable changes in the vulva area. The authors also present algorithms of actions which should be taken in the case of patients suspected of suffering from vulvodynia. There are also described therapeutic methods proposed by various researchers. The authors further emphasize the lack of consensus in an environment of professionals as to the possibility of using operational methods. Attention was also drawn to the possibility of physiotherapy in the treatment of vulvodynia. Moreover, the authors stress that psychological support and psychoeducation might be useful to patients suffering from vulvodynia. The paper also presents alternative methods of therapy such as hypnosis, acupuncture and biofeedback.